ANALISIS PERBANDINGAN DAN EFEKTIVITAS PEMERATAAN PROGRAM KIP KULIAH: STUDI KASUS DI PTN DAN PTS PROVINSI LAMPUNG - Ecta Rianisa, Devi; As’ari, As’ari; Mahmud, Imam; Raidar, Usman; Wibisono, Damar (Triwikrama: Jurnal Ilmu Sosial, 2025)
The Indonesia Smart Card (KIP) Lecture program is a government initiative to increase access to higher education for students from underprivileged families. This study aims to analyze the effectiveness of the KIP Lecture program in equalizing access to higher education by comparing the experiences of recipient and non-recipient students at one of the state and private universities in Lampung Province. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews and literature studies. The results showed that KIP Kuliah plays a role in easing the financial burden of students, allowing them to focus more on academics and increasing involvement in campus organizations. However, there are still significant administrative obstacles, especially in the delay of fund disbursement and the lack of transparency of information regarding aid procedures, which are felt more by students in PTS than PTN. In addition, there are still students from well-off families who receive assistance, causing problems related to targeting accuracy. These findings indicate that although the KIP Kuliah program has contributed to expanding access to education, improvements in the disbursement mechanism, information transparency, and recipient selection are still needed to optimize the benefits. This study recommends improving coordination between the government and educational institutions, reforming the disbursement policy, and strengthening the selection mechanism of KIP Kuliah recipients to increase the effectiveness and equity of the program. Thus, KIP Kuliah can become a stronger instrument in reducing inequality in higher education in Indonesia.